ANALISIS MANAJEMEN PEMBERIAN BANTUAN SEMBAKO OLEH DINAS SOSIAL DAN PEMAKAMAN KOTA PEKANBARU - Fachri Reza; Chalid Sahuri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The problems of poverty are quite complex requires the intervention of all parties together and coordinated. But this tends handling during partial and not sustainable. Therefore to achieve common prosperity and reduce poverty, the central government made a policy such as poverty reduction programs. Of it that the government centered nor the region can be allocated for social assistance to people who are poor to help her life as one of the programs that can help people at least reduce the burden of life and can make people powerless so that people can live your life for the better again.Particularly in the city of Pekanbaru. in 2014 there were 324,000 inhabitants who are poor and continued to increase in 2015 to 327,000 people, out of the total population of Pekanbaru city as much as 975 304 inhabitants ie 33.5% of the total population of the city of Pekanbaru with high rate. Social Service and Funeral Pekanbaru City as the institution that emlakukan task in terms of providing food assistance to the poor in cities Pekanbaru because msih there is the phenomenon of the implementation of the provision of food assistance related to Risk Management, and therefore the author doing research Management Analysis Relief Sembako by the Department of Social Funeral Pekanbaru City in order to know and analyze the management and provision of social assistance hambatanya by the Department of social and Pekanbaru City Cemetery.further research methods used Methods used in this study is a qualitative study that depicts or describes the existing problems by providing answers to the problems dikemukan later in collecting data using interviews and observations writer as research data collection tools.After collecting the data derived from the research informants is Head of Social and Funeral Pekanbaru, Head of Social Assistance and Community that receive food assistance. Can diketahu that is actually in the implementation of the provision of basic food done by the Department of Social and Funeral Pekanbaru city has implemented management functions that are not in melanism which explain the background, but the implementation is very visible, and can be classified in kategroi pretty good. But after doing some research still looks weak management conducted by the Department of Social and funeral Pekanbaru City as data collection is not yet complete so additional planning is not maximized, the division of tasks and teams are not in accordance with the condition of the area.Keyword: management